Case Report: Resuscitation in Intraoperative Third Space Loss in Pediatric Patient with Paracentesis for Massive Ascites - Astrid; Kapuangan, Christopher (Proceedings Book of International Conference and Exhibition on The Indonesian Medical Education Research Institute, 2024)
The accuracy of intraoperative fluid resuscitation is one of the important factors influencing the outcome of surgery. In action conditions with the occurrence of fluid loss from massive "third space loss" in a fast period of time can affect fluid regulation causing ascites re-accumulation hyponatremia, hepato-renal function disorders, to shock. This case report evaluated the success of fluid replacement during massive paracentesis and post-procedure monitoring in the recovery unit. Case description: 5-year-old girl, with massive ascites suspicious of malignancy planned to undergo a paracentesis procedure. The patient had clinical abdominal distention, mild-moderate dehydration, vomiting, and decreased skin turgor. Another abnormality found was a hydrocephalus post-VP Shunt in 2023. The patient was assessed as ASA 3 based on his physical status. Maintenance fluids are calculated to meet basal metabolic needs during surgery based on the Holliday-Segar formula using the 4-2-1 rule. Fluid resuscitation during procedure can be performed with crystalloid, typically 40-60 mL/kg, with a bolus of 10-20 mL/kg to assess fluid responsiveness. In conclusion, fluid administration was carried out using goal-directed fluid therapy, where fluid resuscitation is adjusted based on various hemodynamic parameters.